(untitled) (International journal of artificial intelligence, 2025)
This article explores the critical role of public administration reforms in the transformation of New Uzbekistan. In recent years, the government has launched comprehensive modernization efforts aimed at building an efficient, transparent, and citizen-oriented administrative system. These reforms are vital to strengthening democratic institutions, improving public service delivery, and ensuring inclusive development. The paper analyzes the structure, goals, and expected outcomes of these reforms while considering their broader social, political, and economic impact. It also highlights the importance of digitalization, decentralization, meritocracy, and civic engagement in shaping a responsive public administration aligned with global best practices.